Liquid Processing of Interfacially Grown Iron‐Oxide Flowers into 2D‐Platelets Yields Lithium‐Ion Battery Anodes with Capacities of Twice the Theoretical Value. Issue 39 (1st September 2022) - Konkena, Bharathi; Kaur, Harneet; Tian, Ruiyuan; Gabbett, Cian; McCrystall, Mark; Horvath, Dominik Valter; Synnatschke, Kevin; Roy, Ahin; Smith, Ross; Nicolosi, Valeria; Scanlon, Micheál D.; Coleman, Jonathan N.
Abstract: Iron oxide (Fe2 O3 ) is an abundant and potentially low‐cost material for fabricating lithium‐ion battery anodes. Here, the growth of α‐Fe2 O3 nano‐flowers at an electrified liquid–liquid interface is demonstrated. Sonication is used to convert these flowers into quasi‐2D platelets with lateral sizes in the range of hundreds of nanometers and thicknesses in the range of tens of nanometers. These nanoplatelets can be combined with carbon nanotubes to form porous, conductive composites which can be used as electrodes in lithium‐ion batteries. Using a standard activation process, these anodes display good cycling stability, reasonable rate performance and low‐rate capacities approaching 1500 mAh g −1, consistent with the current state‐of‐the‐art for Fe2 O3 . However, by using an extended activation process, it is found that the morphology of these composites can be significantly changed, rendering the iron oxide amorphous and significantly increasing the porosity and internal surface area. These morphological changes yield anodes with very good cycling stability and low‐rate capacity exceeding 2000 mAh g −1, which is competitive with the best anode materials in the literature. However, the data implies that, after activation, the iron oxide displays a reduced solid‐state lithium‐ion diffusion coefficient resulting in somewhat degraded rate performance. Abstract : This work demonstrates the growth of α‐Fe2 O3 nano‐flowers and their conversion into quasi‐2D platelets. These nanoplatelets are combined with carbon nanotubes to form porous, conductive composites for use in a lithium‐ion battery anode. With a newly developed an extended activation process, these composite electrodes can achieve high capacities, beyond 2000 mAh g −1, which is competitive with the state‐of‐the‐art anode materials.